Development of a Low-fish Meal Feed Formulation for Commercial Production of Litopenaeus vannamei - M. Fox, Joe; L. Lawrence, Addison; Smith, Franz (Avances en Nutrición Acuicola, 2019)
Fish meal is used in marine shrimp feeds because it is high in protein, highly digestible and is an effective feed attractant. Reasons for current interest in its replacement include irregular availability, variable quality, perceived contribution to deterioration of fisheries, potential for adulteration, contamination with hydrocarbons and biological pathogens, and increasing cost. Growth trials were conducted with juvenile Litopenaeus vannamei to evaluate modifications in nutrient supplementation/restriction of a basal fish meal replacement formula at the 50% replacement level. Trials compared growth and survival of shrimp fed a basal control feed to experimental feeds in which crystalline amino acids (CAA), oil and lecithin, blood meal and specific minerals were modified. Improved or similar growth relative to the control feed were shown with reduced levels of CAA, removal of menhaden oil, inclusion of a lower level of lecithin, and maintenance of blood meal and mineral supplements at their basal levels. This information was used to develop a generalized fish meal replacement formulation for marine penaeid shrimp using readily available partiallypurified ingredients. Low- and high-marine animal meal feed formulations are compared.